Views of New South Wales. Vol. II - Bayliss, Charles, 1850-1897.; New South Wales. Government Printing Office (1886)
Views of Sydney buildings, groups of officers and men of 1st Infantry Regiment, Corps of Engineers and Scottish Rifles N.S.W., and Darling River scenes.
Spine title.
Cover: Presented to Major General E.T.H. Hutton, CB, ADC to the Queen, cmdg. military forces of New South Wales, by Major Stephen Mallarky, 2nd Infantry Regiment, March 1896.
Photographers: New South Wales Government Printing Office, Charles Bayliss.
Also available online
Keywords: Hutton, Edward T. H. -- Sir, -- 1848-1923 -- Photograph collections; New South Wales -- Photographs; New South Wales -- Armed Forces -- Photographs